Assessment of Integration-defective HIV-1 and EIAV Vectors In Vitro and In Vivo - Scott Ellis; Liang Fong-Wong; Sharifah Iqball; Vinay Thoree; Kyriacos A Mitrophanous; Katie Binley (Molecular Therapy: Nucleic Acids, 2012)
The interest in integrase-defective lentiviral vectors (IDLVs) stems from their potential advantage of large cloning capacity and broad cell tropism while avoiding the possibility of insertional mutagenesis. Here, we directly compared the transducing potential of IDLVs based on the equine infectious anemia virus (EIAV) to the more commonly described HIV-1 IDLVs. IDLVs were constructed by introducing equivalent single/triple mutations into the integrase catalytic triad. We show that both the single and the triple mutant HIV-1 IDLVs transduce the PC12 cells, but not the C2C12 cells, with similar efficiency to their parental HIV-1 vector. In contrast, the single and triple EIAV IDLVs did not efficiently transduce either differentiated cell line. Moreover, this HIV-1 IDLV-mediated expression was independent of any residual integration activity because reporter expression was lost when cell cycling was restored. Four weeks following stereotactic administration into adult rat brains, only the single HIV-1 IDLV mutant displayed a comparable transduction profile to the parental HIV-1 vector. In contrast, neither EIAV IDLV mutants showed significant reporter gene expression. This work indicates that the transducing potential of IDLVs appears to depend not only on the choice of integrase mutation and type of target cell, but also on the nature of the lentiviral vector.